Not all inequality measures were created equal: The measurement of wealth inequality, its decompositions, and an application to European household wealth - Rita Neves Costa; Sébastien Pérez-Duarte (European Central Bank (ECB), 2019)
Much of the literature on inequality, both that on the theoretical features of inequality measurement and that on the discussion of the results of empirical analysis, has preferred to focus on income inequality. This paper looks into the analysis of wealth inequality, which can be performed by carefully adapting the techniques used in the case of income distributions. The paper focuses on the measurement of inequality itself and includes an application to European data on wealth. We summarise the main inequality measures used in the economic literature, expanding the focus to lesser known but relevant ones, grounding their use in socio-economic theory and highlighting the connections between them. In particular, we investigate how each measure captures the same movement in the wealth distribution and why different measures can lead to differences in the observed change in inequality over time or across countries. In the main theoretical contribution of the paper we obtain a novel decomposition of changes in inequality measures as a set of equalising and disequalising factors, which sheds some light on the different results across indicators. We complement the analysis by focusing on the decomposition of wealth inequality measures, gaining an understanding of the contributions of inequality by wealth component and socio-demographic characteristics. The distribution of wealth of European households obtained by the Household Finance and Consumption Survey (HFCS) in 2010 and 2014 is used for empirical analysis and application of our methods.
Keywords: 330; wealth; inequality; Atkinson; Lorenz curve; Gini coefficient; Pietra index; decomposition